Ensuring a Balance Between the Principle of Good Faith and Abuse of Rights in Ukrainian Court Practice - Vasyliev, Sergii (Problems of legality, 2026)
The article reveals the peculiarities of the functioning of the principle of good faith in substantive and procedural law of Ukraine and defines the tools used in judicial practice to counteract bad faith of participants in legal relations. Good faith is revealed as one of the fundamental principles of law, which, being largely an evaluative category, has not been clearly defined in either substantive or procedural legislation. At the same time, this in no way diminishes its importance, since the principle of good faith serves as a kind of criterion for evaluating the actions of participants in legal relations (including procedural ones) and, if necessary, fills gaps in legal regulation. It is emphasized that in practice, good faith acquires legal significance through the identification of cases of abuse of rights. The author has carried out a theoretical and legal analysis of such phenomena as estoppel, the doctrine of «prohibition of contradictory behavior», and the doctrine of «inadmissibility of exercising a right to cause harm». These tools (1) allow courts to refuse to apply formal rules in cases where this breaks the causal link between the unfair conduct of one party and the negative consequences for the other; (2) serve as an effective means of ensuring good faith conduct by the parties to the proceedings, making it possible to counteract manipulation by the parties, prevent delays in proceedings, and facilitate the adoption of decisions based on an objective assessment of the evidence and the facts of the case. In the author's opinion, the application of this tool requires particular caution given the specific nature of the legal relationship in question, since qualifying a person's conduct as «abuse of rights» and applying the relevant legal instruments may upset the balance between «good faith» and «abuse», allowing for disproportionate restrictions or violations of the rights and legitimate interests of third parties.